2022
DOI: 10.3389/fmed.2022.985361
|View full text |Cite
|
Sign up to set email alerts
|

A case report of cerebral venous sinus thrombosis presenting with rapidly progressive dementia

Abstract: BackgroundCerebral venous sinus thrombosis (CVST) is a rare but serious and treatable cause of neurologic symptoms. Due to the variable clinical presentation, CVST was often misdiagnosed. According to published case reports, common clinical manifestations of CVST include headache, focal neurological deficit, epilepsy, papilledema, etc. It is rare, nevertheless, to mention cases of rapidly progressive dementia (RPD).Case presentationWe reported a case of a 62-year-old retired male accountant, a Han Chinese from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…9 Subacute or chronic cases of severe cognitive dysfunction have also been observed in cerebral venous thrombosis and classified under the category of rapidly progressive dementia. 37 Perhaps the most atypical psychopathological feature of our case is the catatonic syndrome, which has only been reported a few times. Gangadhar et al 6 described the case of an 18-year-old woman who presented with catatonia and had a lethal outcome, and the autopsy diagnosis was cerebral venous thrombosis.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…9 Subacute or chronic cases of severe cognitive dysfunction have also been observed in cerebral venous thrombosis and classified under the category of rapidly progressive dementia. 37 Perhaps the most atypical psychopathological feature of our case is the catatonic syndrome, which has only been reported a few times. Gangadhar et al 6 described the case of an 18-year-old woman who presented with catatonia and had a lethal outcome, and the autopsy diagnosis was cerebral venous thrombosis.…”
Section: Discussionmentioning
confidence: 61%
“…Delirium, which is also known as acute confusional state, has been reported in cerebral venous thrombosis since the publication of a classical series of 38 cases in 1985 9 . Subacute or chronic cases of severe cognitive dysfunction have also been observed in cerebral venous thrombosis and classified under the category of rapidly progressive dementia 37 …”
Section: Discussionmentioning
confidence: 99%
“…When conventional cranial MRI and head CT yield inconclusive results, the possibility of CVT cannot be definitively ruled out, necessitating further assessment through MRV. [6,17] In cases where contrast agents cannot be administered, MRV's sensitivity and specificity diminish, potentially leading to false-negative or false-positive outcomes. [10] In our study aimed at evaluating the impact of the ASL-MRP technique on CVT diagnosis, we observed an increase in CBF in five out of six patients with acute CVT.…”
Section: Discussionmentioning
confidence: 99%
“…[5] However, the identification of CVT can sometimes face delays or challenges due to atypical clinical manifestations. [6] Although computed tomography (CT) and magnetic resonance (MR) angiography are recommended diagnostic tools for detecting CVT, these methods have limitations. [7,8] They include issues such as false negatives/positives, susceptibility to motion artefacts, extended examination times and reduced sensitivity in cases where contrast agents cannot be used, particularly in non-contrast-enhanced time-of-flight (TOF) MR venography (MRV).…”
Section: Introductionmentioning
confidence: 99%